TRANSFORMASI NILAI ADAB DALAM PENDIDIKAN ISLAM MELAYU DI ERA DISRUPSI DIGITAL - Amrillah, M. Soinun; Darmanto; Idi, Abdullah; Asmara, Abdillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The era of digital disruption has created paradigmatic challenges for Islamic education, particularly in maintaining the value of adab (civility) amidst the massive and unfiltered flow of information. This study aims to analyze the transformation of adab values ​​in Malay Islamic education and formulate a strategy for inclusive and adaptive curriculum reorientation amidst the massive information technology boom. Using qualitative methods with a desk study approach, data were analyzed from various scientific literature on the reorientation of Islamic education and the digitalization of local wisdom. The results show that the transformation of adab in the Malay context involves not merely replacing learning media but rather reconstructing educational components that balance technological mastery with character building. The main findings emphasize that hybrid-Islamic Malay local wisdom—namely, the acculturation of local cultural values ​​with Islamic teachings—plays a crucial role as a moral strengthening instrument for Generation Z in stemming deviant behavior in cyberspace, such as hoaxes and the degradation of manners. The manifestation of adab has transformed into